Introduction to renormalization - Holovatch, Yu. (Condensed Matter Physics, 2006)
In these lectures I discuss peculiarities of the critical behaviour of “non-ideal” systems as it is explained by the renormalization group approach. Examples considered here include account of the single-ion anisotropy, structural disorder, frustrations. I introduce main ideas of renormalization and show how it serves the explanation of typical features of criticality in the above systems: softening of the phase transition, changes in the universality class, complicated effective critical behaviour